Control of host PTMs by intracellular bacteria: An opportunity toward novel anti-infective agents. Issue 5 (19th May 2022) - Stévenin, Virginie; Neefjes, Jacques
Summary: Intracellular bacteria have developed a multitude of mechanisms to influence the post-translational modifications (PTMs) of host proteins to pathogen advantages. The recent explosion of insights into the diversity and sophistication of host PTMs and their manipulation by infectious agents challenges us to formulate a comprehensive vision of this complex and dynamic facet of the host-pathogen interaction landscape. As new discoveries continue to shed light on the central roles of PTMs in infectious diseases, technological advances foster our capacity to detect old and new PTMs and investigate their control and impact during pathogenesis, opening new possibilities for chemical intervention and infection treatment. Here, we present a comprehensive overview of these pathogenic mechanisms and offer perspectives on how these insights may contribute to the development of a new class of therapeutics that are urgently needed to face rising antibiotic resistances. Graphical abstract: Abstract : Post-translational modifications (PTMs) provide strategic local, dynamic, and versatile controls of host protein activities to intracellular bacteria. Stévenin and Neefjes provide a comprehensive overview of the bacterial mechanisms controlling host PTMs and discuss how the recently gained knowledge may open new avenues for the discovery and development of anti-infective agents.